Dear friends, Please read our latest blog post for an important announcement about the website. ❤, The Socratic Team

How do you solve #(x-1)/(x+1)= (-3x)/(2x+2) + x/(6x+6)#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
dseah Share
Jun 18, 2018

Answer:

#x=6/14 or x=-1#

Explanation:

Need to get denominator same for the two additions

#(-3x(6x+6)+x(2x+2))/((2x+2)(6x+6))#

#(-18x^2-16x)/((2x+2)(6x+6))#

#(-8x(2x+2))/((2x+2)(6x+6))#

#(-8x)/(6x+6)=(x-1)/(x+1)#

#-8x(x+1)=(6x+6)(x-1)#

#-8x^2-8x=6x^2-6#

#0=14x^2+8x-6#

#0=(14x-6)(x+1)#

Was this helpful? Let the contributor know!
1500
Trending questions
Impact of this question
27 views around the world
You can reuse this answer
Creative Commons License